Microfiltration performance with two-phase flow - Qian, Guanglei (2013)
In this study, a designed membrane module was installed behind a hermetic bioreactor and the residual gas of the bioreactor was used for generating two-phase flow to control membrane fouling. The combination device was operated under gas flowrate 6.9, 11.4 and 15 L/h in order to verify the impacts of gas flowrate on the performance of membrane module. The results showed that the effluent quality was better than the supernatant under the same gas flowrate, while membrane fouling was effectively mitigated by increasing gas flowrate due to the shear force generated by two-phase flow. In addition, the critical flux was observed to have a positive correlation with gas flowrate, which fitted well with the inertial lift model. The concentration of total extracellular polymeric substances (EPSs) in the reactor decreased as gas flowrate increased from 6.9 to 15 L/h, which was a probable index for membrane fouling. The quantity and composition of EPS in the supernatant and membrane surface were significantly different under the same gas flowrate. The accumulation of protein (EPSP) on the membrane surface might change the hydrophobicity of membrane tubes and play an important role in formation of the irreversible fouling layer.